Jaringan Komunikasi Sosial Komunitas Tempe Tenggilis dalam Rangka Bertahan Hidup di Surabaya - Charolin Indah Roseta (IAI Darussalam, 2020)
This paper studies a unique phenomenon that in the middle of economic pressure, a lack of resource access, and high-level life competition, urban migrants can survive in a city by optimizing traditional communication networks in Tempe industry. This field-research study uses a phenomenological approach through participative observation and in-depth interviews. It indicates the patronage pattern, in the form of business patronage system conducted by tempe maker community, gives a chance for migrants to be able to survive in the city. Interaction patterns between soybean suppliers and tempe makers can save them from the crisis. The moral value of “sabaya pati, sabaya mukti” becomes a core message for the clients in conducting verbal and nonverbal communication networks with their patron. This is a sustainable life guarantee so that tempe makers in 3 Tenggilis clusters remain survive in Surabaya with their limits.